Potential distribution of native freshwater fish in Tabasco, Mexico - Paula Andrea Castillo-Torres; Enrique Martínez-Meyer; Fernando Cordova Tapia; Luis Zambrano (Revista Mexicana de Biodiversidad)
The distribution patterns of the freshwater fish within Tabasco wetlands have not being yet studied at a regional scale. We implemented an ecological niche modeling approach to: 1) identify the potential richness distribution patterns of native fish; 2) evaluate the relative importance of climatic and topographic variables in fish distribution, and 3) analyze if the natural protected areas correspond to areas with higher potential species richness. We used occurrence records of 41 native fish species and 22 interpolated surfaces that represent topographic features and annual, seasonal and extreme trends of temperature and precipitation to generate niche-based potential geographic distribution maps using the GARP and MaxEnt algorithms. Our results show that habitat affinities can be detected at the regional scale using macro-climatic and topographic variables. Despite the apparent evenness of the system, species’ distributions were not homogenous at the regional scale. The classification tree analysis showed that the mean temperature of the driest quarter was the most influential variable for clustering species. We found that areas with the highest potential species richness are not included in the natural protected areas network. This information can be used for the development of new and better native fish conservation strategies, like expanding the current ones or establishing new natural protected areas.